A point of care test for interleukin-6 in amniotic fluid in preterm prelabor rupture of membranes: a step toward the early treatment of acute intra-amniotic inflammation/infection. (1st February 2016) - Chaemsaithong, Piya; Romero, Roberto; Korzeniewski, Steven J.; Martinez-Varea, Alicia; Dong, Zhong; Yoon, Bo Hyun; Hassan, Sonia S.; Chaiworapongsa, Tinnakorn; Yeo, Lami
Abstract: Objective : Preterm prelabor rupture of membranes (preterm PROM) accounts for 30–40% of spontaneous preterm deliveries and thus is a major contributor to perinatal morbidity and mortality. An amniotic fluid (AF) interleukin-6 (IL-6) concentration is a key cytokine for the identification of intra-amniotic inflammation, patients at risk of impending preterm delivery and adverse pregnancy complications. The conventional method to determine IL-6 concentrations in AF is an enzyme-linked immunosorbent assay (ELISA). However, this technique is not available in clinical settings, and the results may take several days. A lateral flow-based immunoassay, or point of care (POC) test, has been developed to address this issue. The objective of this study was to compare the performance of AF IL-6 determined by the POC test to that determined by ELISA for the identification of intra-amniotic inflammation in patients with preterm PROM. Materials and methods : This retrospective cohort study includes 56 women with singleton pregnancies who presented with preterm PROM. Amniocentesis was performed at the time of diagnosis, and AF was analyzed using cultivation techniques for aerobic and anaerobic bacteria as well as genital mycoplasmas. AF Gram stain and AF white blood cell counts were determined. AF IL-6 concentrations were measured using both lateral flow-based immunoassay and ELISA. The primary outcome was intra-amniotic inflammation defined as AF ELISA IL-6 ≥ 2600 pg/ml. A previously determined cut-off of 745 pg/ml was used to define a positive POC test. Results : (1) The POC test for AF IL-6 concentrations had 97% sensitivity and 96% specificity for the identification of intra-amniotic inflammation, as defined using ELISA among patients with preterm PROM and (2) the diagnostic performance of the POC test for IL-6 was strongly correlated to that of an ELISA test for the identification of intra-amniotic inflammation and was equivalent for the identification of acute inflammatory placental lesions and microbial invasion of the amniotic cavity (MIAC). Conclusion : A POC AF IL-6 test can identify intra-amniotic inflammation in patients with preterm PROM. Results can be available within 20 min – this makes it possible to implement interventions designed to treat intra-amniotic inflammation and improve pregnancy outcomes.